2007
DOI: 10.1073/pnas.0610785104
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sequestration of defensive steroids in nuchal glands of the Asian snake Rhabdophis tigrinus

Abstract: The Asian snake Rhabdophis tigrinus possesses specialized defensive glands on its neck that contain steroidal toxins known as bufadienolides. We hypothesized that R. tigrinus does not synthesize these defensive steroids but instead sequesters the toxins from toads it consumes as prey. To test this hypothesis, we conducted chemical analyses on the glandular fluid from snakes collected in toad-free and toad-present localities. We also performed feeding experiments in which hatchling R. tigrinus were reared on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
81
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 26 publications
0
81
0
4
Order By: Relevance
“…1). In addition to Afro-Asian varanids (17), we find convergent resistance-conferring amino acid changes in the phylogenetically distinct viperid, elapid, and natricine snake lineages (including members of the toad toxin sequestering genus Rhabdophis) (19), representing convergent molecular evolution over ∼165 million years of separation (20). This constitutes compelling evidence of adaptive molecular convergence underlying phenotypic convergence.…”
Section: Resultsmentioning
confidence: 99%
“…1). In addition to Afro-Asian varanids (17), we find convergent resistance-conferring amino acid changes in the phylogenetically distinct viperid, elapid, and natricine snake lineages (including members of the toad toxin sequestering genus Rhabdophis) (19), representing convergent molecular evolution over ∼165 million years of separation (20). This constitutes compelling evidence of adaptive molecular convergence underlying phenotypic convergence.…”
Section: Resultsmentioning
confidence: 99%
“…Each individual has a series of 10 -20 pairs of these nuchal glands that extends caudally behind the head (Nakamura 1935;Smith 1938;Toriba and Sawai 1990). The contents of the nuchal glands irritate mucous membranes, cause corneal injuries (Nakamura 1935;Kitazume 1953;Kawashima 1957Kawashima , 1959Suzuki 1960;Asahi et al 1985), and contain cardiotonic steroids known as bufadienolides (Akizawa et al 1985a,b;Hutchinson et al 2007). Bufadienolides act by inhibiting the sodiumpotassium pump in a digitalis-like fashion (Melero et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…107 Mori and Burghardt, 108 however, postulated that this snake acquires these compounds from toads, sequestering them from their prey for defense against their predators. Hutchinson et al 107 investigated this hypothesis by comparing the nuchal gland fluids of wildcaught snakes from areas in Japan inhabited by toads with fluids from snakes inhabiting Kinkazan Island, where toads are absent. All snakes except those from Kinkazan possessed bufadienolides 76-95.…”
mentioning
confidence: 99%
“…Laboratory studies demonstrated that hatchling yamakagashis, even those from Kinkazan, rapidly and consistently accumulated bufadienolides in their nuchal glands when reared on North American toads (Bufo fowleri and B. terrestris), but not on prey (fish or frogs) that lack these compounds. 107 The toads contain mostly the conjugated bufadienolides 96-103 and 82. Yamakagashis that were fed toads accumulated 76-78, 83, 86-88, and 91 in their nuchal glands, none of which they possessed upon hatching.…”
mentioning
confidence: 99%